1986
DOI: 10.1111/j.1699-0463.1986.tb02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte‐labelling Index in the Duodenal Mucosa of Patients With Progressive Systemic Sclerosis (Pss)

Abstract: Ten patients with progressive systemic sclerosis (PSS), 4 patients with other gastro‐intestinal diseases and 5 normal controls, underwent small intestinal biopsy procedure. The biopsy material was incubated with tritiated thymidine and processed for auto‐radiography. The labelling index (LI) in the small intestinal mucosa was estimated. The LI in PSS patients with duodenal involvement was significantly higher than the LI in PSS patients without duodenal involvement. In the latter group, the LI was at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The esophagus is involved in about 70% of all PSS cases, the small and !arge intestine in about 40% and 100%, respectively (1). In a previous study we demonstrated the esophageal mucosa from PSS patients with esopha geal involvement to contain a higher concentration of collagen than esophageal mucosa from PSS patients without involvement (2). In the present study, we determined the concentrations of amino acids characteristic of collagen in the duodenal and rectal mucosa of PSS patients and of patients with various other diseases.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The esophagus is involved in about 70% of all PSS cases, the small and !arge intestine in about 40% and 100%, respectively (1). In a previous study we demonstrated the esophageal mucosa from PSS patients with esopha geal involvement to contain a higher concentration of collagen than esophageal mucosa from PSS patients without involvement (2). In the present study, we determined the concentrations of amino acids characteristic of collagen in the duodenal and rectal mucosa of PSS patients and of patients with various other diseases.…”
mentioning
confidence: 72%
“…In the present study, we determined the concentrations of amino acids characteristic of collagen in the duodenal and rectal mucosa of PSS patients and of patients with various other diseases. The aim of the study was to investigate whether changes in collagen concentration in the surface layers of the gastroin testinal tract is a characteristic feature in PSS (2,3).…”
mentioning
confidence: 99%
“…The frequency of esophageal dysmotility is 46-92%, 30-88%, 21-72%, and 50% in patients with systemic sclerosis (SSc), mixed connective tissue disease (MCTD), systemic lupus erythematosis (SLE), and polymyositis/dermatomyositis (PM/DM), respectively [1][2][3][4][5][6][7][8]. While the cause of esophageal dysfunction in patients with CTDs has been unclear, there are some reports that suggest the accumulation of extracellular matrix, neuropathy, and autoantibody as the cause of esophageal dysfunction in patients with SSc [9][10][11]. On the other hand, there are few reports relating to the cause of esophageal dysfunction in MCTD patients, despite its frequency.…”
Section: Introductionmentioning
confidence: 99%